Stock Market Development, Growth and Financial Openness: The Experience of Selected East Asian Nations - Noor A. Ghazali,; Rasidah M. Said,; Soo-Wah Low, (Asian Academy of Management Journal of Accounting and Finance, 2007)
The finance-growth nexus that argue on the real effect of finance is examined in this study. Specifically, we investigated two related links; stock market development-growth link and financial openness-stock market development link for six East Asian nations (Indonesia, South Korea, Malaysia, Philippines, Singapore and Thailand) from 1985–2000. Our results support the proposition that stock market development influenced the real sector in all countries except for Indonesia. With respect to financial openness, our results are mixed. Only Malaysian stock market shows consistent gain from financial openness. There is no significant influence of financial openness on Singapore's stock market development. For all other countries the effect are mixed varies according to measurements used. Each country's experience is unique and consequences of financial openness are critically influenced by underlying country-specific factors. Thus, the effect of financial openness is not common among these East Asian nations. Further investigations that entertain country-specific factors are necessary prior to conclusive view on the effect of financial openness.